Should obesity affect suitability for kidney donation?. Issue 4 (28th May 2018) - Sachdeva, Mala
Abstract: As with the suitability for kidney transplantation for obese recipients, there is no universally accepted guideline for clinicians for obese donors; criteria for acceptance are variable among transplant centers. Obesity is on the rise in the United States and the number of living kidney donors who are obese parallel this national trend. Careful risk assessment and informed consent must be undertaken predonation prior to accepting an obese kidney donor in order to minimize long‐ and short‐term complications. Likewise, close postdonation follow‐up for this higher risk group should be implemented.